5 - Histoire et mémoire de Gorée dans la traite atlantique :paramnésie de localisation - Bassène, Pape Chérif Bertrand (Africa Development, 2021)
The controversy of “Gorée and slavery: Myths and Realities” had two effects. It actually fuelled a denial of the memory of Gorée while in the scientific ambit which is often the preserve of universities; researchers have tried to study the relationship between history and memory in the perception of the island’s past. In this respect, this reflection proposes to relocate the theme of Gorée and slavery in the historical context of the Concession of Senegal. This is a prerequisite to understanding of both historical and symbolic (memorial through the Slave House) role of Gorée Island and the Atlantic slave trade. After demonstrating how Gorée has become a major slave transit point, we can now better explain why the much-criticized remembrance speech of the Slave House far from creating a Gorée Island myth rather attempts to symbolically give a weight to suffering.